Zellweger syndrome and associated phenotypes. Issue 10 (October 1996) - FitzPatrick, D R
Abstract : Until recently, the peroxisome was considered a "reactor chamber" for H2O2 producing oxidases, and it is now recognised as a versatile organelle performing complex catabolic and biosynthetic roles in the cell. Zellweger syndrome (ZS), the paradigm of human peroxisomal disorders, is characterised by neonatal hypotonia, severe neuro-developmental delay, hepatomegaly, renal cysts, senorineural deafness, retinal dysfunction, and facial dysmorphism. It is now clear that ZS is at the severe end of a phenotypic spectrum of Zellweger-like syndromes which may present for diagnosis later in childhood and even in adult life. It is important that clinical geneticists are aware of these milder clinical variants as the availability of sensitive and specific biochemical assays of peroxisomal function (for example, serum VLCFA ratios, platelet DHAP-AT activity) makes their diagnosis relatively straightforward.